Analysis of the Connecting, Organizing, Reflecting and Extending (CORE) Model to Improving the Mathematical Reasoning Ability Students - Atiyah, Khairini; Priatna, Nanang (SJME (Supremum Journal of Mathematics Education), 2023)
The low of students' reasoning ability is caused by the teacher's lack of ideas in applying the learning model in the class. This study aims to conduct a literature review on the improvement in students' of senior high school on mathematical reasoning ability after got the connecting, organizing, reflecting and extending (CORE) model and to determine the advantages of the CORE model in mathematics learning in the class. The research used is a qualitative using the systematic literature review (SLR) method with a survey-based descriptive approach. The survey was conducted on secondary data, namely the results of basic research on the CORE model on students' mathematical reasoning abilities. The research technique used data collection, data analysis, and drawing conclusions. The results indicate that the student's responses to the CORE learning model were positive. Based on the research criteria from 8 articles, students’ can improve the mathematical reasoning after got the connecting, organizing, reflecting and extending (CORE) model, compared to students received conventional mathematics learning and the advantages of the CORE model in the class, namely developing students' activeness in learning, training memory, developing students' reasoning power, developing reasoning mathematical skills with the stages of connecting, organizing, reflecting and extending.